Effect of different type of solvents on asymmetric polysulfone membrane for co2/ch separation - Sharifah Ainun Nor, Khaidzi (2010)
The objective of this study is to develop a high performance and defect free asymmetric polysulfone membrane for CO2/CH4 separation and to investigate the effect of different type of solvents on the performance of the polysulfone membrane. The membrane were developed consist of 20% polsulfone (PSU) polymer, 77% solvent (NMP, DMAc, DMF) and 3% water (H20) as non-solvent additive. Firstly, three type of casting solution had been developed by manipulating a different type of solvent which consist of N-methyl-2-pyrrolidone (NMP), N-N-Dimethylformamide (DMF) and N-Dimethylacetamide (DMAc). Formation of the asymmetric flat sheet membrane had been performed using casting block through a simple dry/wet phase inversion process. Water and methanol were used as solvent for solvent exchange process. On the next stage, pure CO2 and CH4 were used as test gases in the permeation test using pressure supply range between 1 to 4 bar. Consequently, the result showed that the asymmetric flat sheet membrane developed by using N-methyl-2-pyrrolidone (NMP) as a solvent achieved better performance in terms of permeability and selectivity of the membrane which is 7.34. The produced asymmetric polysulfone membranes were then carry out by characterized using Scanning Electron Microscopic (SEM) to investigate the structure and morphology of the membrane. Based on SEM images, it can observe that the membrane with N-methyl-2-pyrrolidone (NMP) as a solvent has the most porous structure. Finally, the membrane structure was further characterized the rheological induced molecular orientation in asymmetric membrane that observed by analyzing the wave length using Fourier Transform Infrared Spectroscopy (FTIR). As a conclusion, the polysulfone membrane prepared from PSU/NMP/H2O solvents system proved to give greatest separation characteristics compared to other membrane produced from PSU/DMAc/H2O and PSU/DMF/H2O solvent systems.